2013
DOI: 10.1111/tmi.12199
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of moderate‐to‐severe anaemia among women of reproductive age in Tanzania: analysis of data from the 2010 Tanzania demographic and health survey

Abstract: Abstractobjective To identify determinants of moderate-to-severe anaemia among women of reproductive age in Tanzania.methods We included participants from the 2010 Tanzania Demographic and Health Survey, which collected data on socio-demographic and maternal health and determined haemoglobin levels from blood samples. We performed logistic regression to calculate adjusted odds ratios for associations between socio-demographic, contextual, reproductive and lifestyle factors, and moderate-to-severe anaemia and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 33 publications
22
30
0
Order By: Relevance
“…In this study, the use of hormonal contraceptives was associated with lower risk of anemia among WRA, while the use of IUDs was associated with higher risk. Using hormonal contraceptive can be resulted in less bleeding during the menstruation, which ultimately reduces blood loss over time (29,30); similar findings were seen in other studies conducted in 14 different low-and middle-income countries including Tanzania and Ethiopia (31) (24)(32). Another study conducted in seven countries also found that hormonal contraceptive users had higher haemoglobin and ferritin levels compared to non-users (33).…”
Section: Discussionsupporting
confidence: 81%
“…In this study, the use of hormonal contraceptives was associated with lower risk of anemia among WRA, while the use of IUDs was associated with higher risk. Using hormonal contraceptive can be resulted in less bleeding during the menstruation, which ultimately reduces blood loss over time (29,30); similar findings were seen in other studies conducted in 14 different low-and middle-income countries including Tanzania and Ethiopia (31) (24)(32). Another study conducted in seven countries also found that hormonal contraceptive users had higher haemoglobin and ferritin levels compared to non-users (33).…”
Section: Discussionsupporting
confidence: 81%
“…Anaemia is usually associated with disadvantaged populations where people of lower education and income are at increased risk for anaemia. Previous studies conducted in Tanzania (14), Mali (15), and India (16) showed higher risk of anaemia among non-educated and poor women. It is possible that non-educated and poor women have lower access to health information and healthcare facilities compared to educated and wealthy women.…”
Section: Discussionmentioning
confidence: 75%
“…One possible explanation is that women with severe anemia avoid pregnancy for health reasons or women are more cognizant of the importance of and responsibility involved in treating anemia during pregnancy, although the effect could be exactly the opposite in that severe anemia has a negative effect on fertility. The findings in a study from Tanzania that looked at factors associated with moderate and severe anemia in women of childbearing age pregnant women found that pregnant women had significantly more moderate to severe anemia [35].…”
Section: Discussionmentioning
confidence: 98%